RECOGNIZING AND DESCRIBING THE DESIRABLE MODEL OF WORKPLACE SPIRITUALITY, CUSTOMER RELATIONSHIP MANAGEMENT AND QUALITY OF WORK LIFE - shahrokhi, Hojat; Pourkiani1, Masoud; Sayadi, Saeed (Revista Inclusiones, 2019)
The present study aims to identify and describe the desired pattern of workplace spirituality, customer relationship management and quality of work life in Kerman Health Insurance Organization.The research method is based on the purpose of applied research and developmental research, and in terms of data collection it is a descriptive-correlation research. The statistical population of this study was 204 employees employed by health insurance organization of Kerman province and random sampling method was proportional to population size and sample size was 132 people. The instrument of measurement and measurement in this study was a standard questionnaire. To assess the validity of the questionnaire, experts and experts used for content validity. To estimate the reliability coefficient, Cronbach’s alpha, structural reliability and composite stability have been used to obtain appropriate grades. In order to perform statistical analyzes, research questions were tested and the model was presented using exploratory and confirmatory factor analysis (using structural equation modeling (SEM)) and SPSS and AMOS software. The results of the research in the proposed model showed that the spirituality of the work environment has a positive and significant effect on the quality of work life, with the highest impact and through indirect customer relationship management in the health insurance organization.